Analisis Komunikasi Penerimaan Aktif Melalui Dakwah Media Tiktok - Bella Salsa Risnawati; Nasichah Nasichah; Mohammad Zaqwani Al-Ghifari (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Dakwah is also one of the content that is interested in the media Tiktok. TikTok has now appeared a lot of content in the form of lectures and discussions. In the consumption of the content of the message communication will be divided into two: active participant and not. This research using qualitative research methods is a way to find a deep understanding of the symptoms of fact or reality. A total of 20 participants were asked for testimonies and opinions through interviews that were conducted either directly or indirectly. The results of the subsequent interviews are reviewed and analyzed based on theories related to the research. The results of the research found that communicators have become active recipients in receiving preaching content through touch media.